2022
DOI: 10.1007/s11071-022-07955-w
|View full text |Cite
|
Sign up to set email alerts
|

Discretized locally active memristor and application in logarithmic map

Abstract: We investigate the properties of the BCZ map. Based on our findings, we define the moduli space associated with its excursions. Subsequently, we utilize the framework we build to establish a discretized analog of the Riemann hypothesis (RH) that holds in a stronger sense from a dynamical perspective. The analog is founded upon a reformulation of the RH, specifically in terms of estimates of L 1 -averages of BCZ cocycle along periodic orbits of the BCZ map. The primary tool we will rely on is the generalized ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 69 publications
0
13
0
1
Order By: Relevance
“…[37][38][39][40][41][42] Therefore, discrete neuron models are more suitable for simulating large-scale neu-ral networks and conducting general research, such as generating chaotic trajectories, pattern recognition, and analyzing synchronized firing behaviors. [43][44][45][46][47][48][49][50][51] As a result, research on discrete neurons has become a hot topic in recent years. In discrete memristor-coupled neural networks, complex dynamical behaviors have been discovered, including coexisting attractors, [52][53][54][55][56] synchronization transitions, and synchronization coexistence.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42] Therefore, discrete neuron models are more suitable for simulating large-scale neu-ral networks and conducting general research, such as generating chaotic trajectories, pattern recognition, and analyzing synchronized firing behaviors. [43][44][45][46][47][48][49][50][51] As a result, research on discrete neurons has become a hot topic in recent years. In discrete memristor-coupled neural networks, complex dynamical behaviors have been discovered, including coexisting attractors, [52][53][54][55][56] synchronization transitions, and synchronization coexistence.…”
Section: Introductionmentioning
confidence: 99%
“…Their results shows that two m-Rulkov neurons can achieve synchronization only when electrically coupled, but not when chemically coupled. Li et al [36] used discrete locally active memristor to construct a logarithmic map, and the coexisting attractors were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have shifted their focus to discrete memristors. Introducing discrete memristors to different maps, it was found that discrete memristive chaotic systems have the advantages of high complexity [49][50][51], coexisting attractors [52][53][54], and offset boosting [55]. Furthermore, Peng et al [56] also studied parameter identification for discrete memristive chaotic maps.…”
Section: Introductionmentioning
confidence: 99%